Pulmonary aspergillosis: reports of two cases from a primary care center of Bangladesh - Podder, Chinmay Saha; Chowdhury, Nandini; Chowdhury, Ananya (BIRDEM Medical Journal, 2021)
Pulmonary aspergillosis is an uncommon condition and at the same time very much challenging to diagnose and difficult to treat. Here, we present two cases of chronic pulmonary aspergillosis, who presented with with chronic low-grade fever, refractory and distressing cough and haemoptysis. The first patient was diagnosed as having aspergilloma in a pre-existing healed tubercular cavity and the second one with subacute necrotizing pulmonary aspergillosis, which simulated as bronchial carcinoma. BIRDEM Med J 2021; 11(3): 227-230